Variability of phenolic and alkaloid content in different plant parts of Carissa edulis Vahl and Zanthoxylum chalybeum Engl. - Ssali Nantongo, Judith; Odoi, Juventine Boaz; Abigaba, Grace; Gwali, Samson (BMC research notes, 2018)
The objective of the study was to investigate the relative abundance and effect of post-harvest treatment on total phenolics (TP) and total alkaloids in the leaves and bark of Carissa edulis and Zanthoxylum chalybeum, which would give an indication of the suitability of leaves as alternative sources of medicine in these plant species. Results: Results indicated higher levels of total phenolics than total alkaloids in both of the species under both freezing and air drying conditions. While more alkaloids were found in leaves compared to bark, there was no difference in abundance of phenols between the plant parts of both species. Air drying preserved more TPs than freezing and the opposite was true for alkaloids. For sustainability, leaves are recommended as an alternative source of medicine instead of the preferred root or stem bark. However, the choice of whether to dry or freeze will depend on the specific compound of interest. Assessment of spatial variability of medicinal properties is highly recommended.
Keywords: Phenols; Alkaloids; C. edulis; Z. chalybeum